The effect of lamination thickness of transformer core on the flux and power loss distribution using grain-oriented 3.1% silicon iron - Nor Ashbahani, Mohamad Kajaan
In this project, the 100kVA three phase transformer core model have been investigated and analyzed for its losses and flux distribution using different thickness lamination of the core built with grain-oriented silicon iron (3.1% SiFe), grade M4. The transformer core has been assembled with 60o T-joint, mitred overlap corner joints using two different thickness of transformer core material, which is 0.23mm and 0.27mm. This research was done with 3D FEM software approaches and experimental methods. From 3D Finite Element Method (FEM), the total magnetic flux density when transformer core assembled with different lamination thickness is obtained. Based on FEM, thinner lamination steel shows better magnetic flux density compared to using thicker lamination steel by percentage of 2.9%. Experimental has been carried out using no load test with arrays of search coil that has been placed to the lamination of the transformer core in order to measure localized and normal flux density distribution and also its odd harmonic content. Localized power loss distribution at the transformer core also done by using thermistor method. Building factor for the transformer core that used thinner lamination steel is better by 2.5% compared to the thicker lamination steel. The experimental results show that when the core flux density increased from 1.0T to 1.8T, the flux distribution in the lamination will show interesting trend at both T-joint and corner joint. The performance at the corner joint shows better result, where high loss will tends to occur more at the T-joint area. The highest losses and flux distribution will occur during 1.8T and the lowest is during 1.0T respectively for both lamination thicknesses. Losses mostly high at the intersection of the joint and will gradually decrease as it travel away from the joint area as indicated by 3D FEM software. Overall, the transformer core that assembled with 0.23mm lamination steel will generate more efficient distribution transformer since it produce lower losses and better flux distribution compared to 0.27mm lamination steel. Therefore, the results obtained by experiment comply with the simulation result obtained by FEM software. In term of economic aspects, large amount of money can be saved when the distribution transformer core been replaced with thinner lamination steel.